The role of Accounting Information Systems and HR Competence in Enhancing Financial Reporting Quality with The Implementation of SAK EMKM on MSME Kabupaten Bandung - Noviana Nur Arifa; Muhammad Iqbal Alamsyah (Jurnal Mirai Management, 2023)
With 99% of all business units being MSMEs, their contribution to Indonesia's economic growth is highly significant. MSMEs provide 60.5% of the GDP and 96.9% of the nation's employment to GDP and employment, respectively. The very large role of MSMEs in economic growth in Indonesia, there are also challenges faced by MSMEs, including capital, human resources, law, and accountability. Constraints in accountability are one of the most common problems faced by SMEs. This problem occurs because MSMEs are not used to recording and compiling financial reports as a description of the company's business and financial conditions. This study aims to determine the role of Accounting Information Systems and HR Competence in Enhancing Financial Reporting Quality with the Implementation of SAK EMKM on MSME Kabupaten Bandung. The research's methodology is quantitative. 17,757 MSMEs made up the study's sample. Nonprobability sampling, in particular purposeful sampling, is used in this investigation. 100 participants made up the study's sample, and their responses were examined using the SmartPLS 4.0 program. The findings indicate that the accounting information system has no significant effect on the financial reporting quality, the accounting information system has a significant effect on the implementation of SAK EMKM, HR competence has a significant effect on the financial reporting quality, and HR competence has a significant effect on the implementation of SAK EMKM. In addition, the results of the study show that the accounting information system and HR competence have a significant effect on the financial reporting quality which is mediated by the implementation of SAK EMKM., Quality of the MSME financial reports in Bandung Regency can be created with components support, namely financial accounting standards, accounting information systems, and quality human resources. MSME actors need to apply these components so that they have good-quality financial reports and can make it easier to analyze their business development and make it easier to get loan funds. Kata Kunci: Accounting Information System, Human Resources Competence, Implementation of SAK EMKM, Financial Reporting Quality